Answer:
Explanation:
a) A is accurate because the half of the Moon that is facing the sun is it by the sun, and the other half is dark.
D. dull and brittle when solid
Answer:
4 kg → +4 m/s
5 kg → -5 m/s
Explanation:
The law of conservation of momentum states that:
- m₁v₁ + m₂v₂ = m₁v₁' + m₂v₂'
- left side → velocities before collision
- right side → velocities after collision
You'll notice that we have two missing variables: v₁' & v₂'. Assuming this is a perfectly elastic collision, we can use the conservation of kinetic energy to set the initial and final velocities of the individual bodies equal to each other.
Let's substitute all known variables into the first equation.
- (4)(-6) + (5)(3) = (4)v₁' + (5)v₂'
- -24 + 15 = 4v₁' + 5v₂'
- -9 = 4v₁' + 5v₂'
Let's substitute the known variables into the second equation.
- (-6) + v₁' = (3) + v₂'
- -9 = -v₁' + v₂'
- 9 = v₁' - v₂'
Now we have a system of equations where we can solve for v₁ and v₂.
- -9 = 4v₁' + 5v₂'
- 9 = v₁' - v₂'
Use the elimination method and multiply the bottom equation by -4.
- -9 = 4v₁' + 5v₂'
- -36 = -4v₁' + 4v₂'
Add the equations together.
<u>The final velocity of the second body (5 kg) is -5 m/s</u>. Substitute this value into one of the equations in the system to find v₁.
- 9 = v₁' - v₂'
- 9 = v₁' - (-5)
- 9 = v₁' + 5
- 4 = v₁'
<u>The final velocity of the first body (4 kg) is 4 m/s.</u>
<u></u>
We can verify our answer by making sure that the law of conservation of momentum is followed.
- m₁v₁ + m₂v₂ = m₁v₁' + m₂v₂'
- (4)(-6) + (5)(3) = (4)(4) + (5)(-5)
- -24 + 15 = 16 - 25
- -9 = -9
The combined momentum of the bodies before the collision is equal to the combined momentum of the bodies after the collision. [✓]
In order to calculate the weight, we may simply use:
W = mg
W = 30 * 9.81
W = 294.3 N
The sum of the reaction force and the upward component of child pulling will be equal to total downward force. The force acting downwards is the weight. Therefore:
R + 12sin(45) = 294.3
R = 285.82 N
The acceleration can be found using the resultant force and the mass of the sled. The resultant force is:
F(r) = pulling force + pushing force - friction
F(r) = 12cos(45) + 8 - 5
F(r) = 11.48 N
a = F/m
a = 11.48 / 30
a = 0.38 m/s²